The Unity of Evidence and the Reflection of Its Reasoning in the Chapter of Suretyship: A Comparative Jurisprudential Study - Muqdadi, Mohamed; Talafha, Mohammad (Jordan Journal of Islamic Studies, 2025)
This study aims to clarify the concept of unified evidence and the reflection of its reasoning in the chapter of suretyship (kafālah), to analyze the opinions of juristic schools, and to explain their respective justifications in pursuit of the most valid interpretation. The study comprises a preliminary section, two main sections, and a conclusion. The preliminary section addresses the definition of unified evidence and the reflection of reasoning based on evidence. The first section discusses the nature of the suretyship contract, while the second section tackles the knowledge of the object of surety. The study adopts a descriptive methodology based on induction, analysis, deduction, and comparison by examining the relevant legal texts related to suretyship and comparing juristic opinions to determine the soundest view. The study concludes that the unity of evidence refers to the agreement of two or more parties in reasoning based on the same piece of evidence, and that there are cases within the field of suretyship where the evidence was unified, but the jurists differed in interpreting it—these cases were thoroughly examined.